DIAGNOSING UNIVERSITY STUDENTS’ ZONE OF TOLERANCE FROM UNIVERSITY LIBRARY SERVICES - Nadiri, Halil; Mayboudi, Seyed Muhammad Ali (Malaysian Journal of Library and Information Science, 2010)
Higher education is a dynamic fast growing service industry and every day it is more and more exposed to the globalization processes. Almost with every sector we face increased competition that also shows itself in higher education as well. Thus, measuring the quality of service in higher education is increasingly important and students should be considered as customers in the field of higher education. Many researchers suggest that for market orientation and differentiation, higher educational institutions should understand their customers, assess their needs, modify their offerings to meet those needs, and thereby boost customer satisfaction by delivering superior quality services. According to research findings service quality of library facilities is one of the most important factors that have a significant influence on students’ overall satisfaction from their universities. The most widely known and discussed scale for measuring service quality -SERVQUAL- has not been successfully adapted to and validated in the library context. The LibQUAL+ scale has been validated in some of the developed cultures but not in other cultural settings. So, there is a significant gap in the literature regarding this area of research. The present study addresses this gap by applying the LibQUAL+ among 358 students of a state-owned university in Northern Cyprus. A conceptual model LIBZOT is presented in this study, and the results demonstrate that evaluation of services can be scaled according to different types of expectations—‘desired’ and ‘adequate’—and that students use these two types of expectations as a comparison standard in evaluating library services. The findings reveal that students have a narrow zone of tolerance with regards to the services provided by libraries.